Cross-sectional study of mammographic breast density of Pakistani women and its association with breast cancer - Humera Naz Altaf,; Raheela Aqeel,; Fareeha Farooqui,; Sehrish Latif,; Sania Waseem,; Arif Malik, (Journal of the Pakistan Medical Association, 2023)
Objectives: To explore if a positive association existed between breast cancer and increased breast density. Method: The retrospective cross-sectional study was conducted at Shifa International Hospital, Islamabad and comprised data from July 10, 2018, to July 10, 2020, of all patients who underwent mammography for screening or diagnostic purposes. Data was collected by reviewing patients’ charts, and was divided into diagnostic group A and screening group B according to mammography target. Breast Imaging Reporting and Data System category was also noted. Data was analysed using SPSS 21. Results: Of the 1,035 women with mean age 46.8±2.5 years (range: 35-82 years), 928(89.7%) were in group A and 107((10.3%) were in group B Prevalent breast densities overall were category A 67(6.3%), B 349(33.7%), C 530(51.2%) and D 89(8.5%). In group A, a lump was detected in 542(58.4%) patients. Of them, 367(67.7%) lesions were malignant and 175(32.3%) were benign. Breast density and malignant tumours had significant association (p<0.05). Conclusion: Mammographic breast density wsa found to have a significant association with breast cancer. Key Words: Breast density, Bcancer, BIRADS, Malignant, Mammography.